Efektivitas Organisasi Dinas Pendapatan Daerah (Dispenda) Kota Palembang Dan Faktor-Faktor Yang Mempengaruhinya - Ikhsan Syamsudin (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Data obtained from a sample of 24 staff employees of the Palembang City regional revenue office who have been analyzed using descriptive analysis. The research results can be concluded that the organization of income management in PalembangCity has a fairly low level of effectiveness. The levbel of organizational effectiveness can be seen from the low contribution of local taxes collected directly by by the regionalrevenue office to PAD during the last five years on average of 26.6%. The small contribution of local taxes to PADshows the dependence of local governments on donations and assistance from the central government became very big. The current organizational srtructure for regional approaches in Palembang is swelling, compared to the previous organizational structure. Leaders pay very little attention to staff in terms of providing motivation to improve their performance, furthermore, it seems that they are unable to provide regular guidance. Keywords : Effectiveness, contribution,governments and leader